Anion inhibition studies of the β-carbonic anhydrase from the pathogenic bacterium Vibrio cholerae. Issue 5 (1st March 2016) - Vullo, Daniela; Del Prete, Sonia; De Luca, Viviana; Carginale, Vincenzo; Ferraroni, Marta; Dedeoglu, Nurcan; Osman, Sameh M.; AlOthman, Zeid; Capasso, Clemente; Supuran, Claudiu T.
Graphical abstract: Abstract: The genome of the pathogenic bacterium Vibrio cholerae encodes for three carbonic anhydrases (CAs, EC 4.2.1.1) belonging to the α-, β- and γ-classes. Here we report and anion inhibition study of the β-CA, VchCAβ with anions and other small molecules which inhibit metalloenzymes. The best VchCAβ anion inhibitors were sulfamide, sulfamate, phenylboronic acid and phenylarsonic acid, which showed K I s in the range of 54–86 μM. Diethyldithiocarbonate was also an effective VchCAβ inhibitor, with an inhibition constant of 0.73 mM. The halides, cyanate, thiocyanate, cyanide, bicarbonate, carbonate, nitrate, nitrite, stannate, selenate, tellurate, divanadate, tetraborate, perrhenate, perruthenate, peroxydisulfate, selenocyanide, trithiocarbonate, and fluorosulfonate showed affinity in the low millimolar range, with K I s of 2.3–9.5 mM. Identification of selective inhibitors of VchCAβ (over the human CA isoforms) may lead to pharmacological tools useful for understanding the physiological role(s) of this under-investigated enzyme.